Implementasi Model Manajemen POAC (Planning, Organizing, Actuating, Controlling) dalam Program “Sekolah Qur’an Keluarga” Berbasis Tafsir Tematik Q.S. Luqman - Nandipah Roa'zah; Muslimatun Diana Muazaroh; Diana Elfiyatul Afifah; Sukirno Sukirno; Moh.Agil Nuruzzaman; Supeno Supeno; Munahar Munahar; Fina Ni'matus Sa'adah (BADAN PENERBIT STIEPARI PRESS, 2021)
The implementation of the POAC management model (Planning, Organizing, Actuating, Controlling) in Islamic educational programs effectively supports structured and value-based learning environments. In programs like the